(untitled) (Research, Society and Development, 2022)
This work was carried out to estimate genetic parameters for the germination of seeds of four varieties of bell pepper to assist in choosing the most suitable genetic material for regions with high temperatures. The study covered two experiments, each comprising a germination temperature of 35.0 °C and an ambient temperature with an average of 19.6 °C, for the cultivars All big, Amarelo Alegria, Casca dura Ikeda and Yolo wonder. The design used was randomized, with eight replicates composed of 25 seeds each, totaling four treatments with 200 seeds per experiment. The germination percentage of the seeds was evaluated at temperatures of 19.6 °C and 35.0 °C, later used to obtain the genetic parameters. Bell pepper cultivars showed significant genetic variation to the detriment of the environmental one, showing that the genetic factor contributed more than the environmental factor to the studied correlation. Despite the low percentage of germination observed at 35.0 °C, the highest values were obtained for the cultivars All big, and Yolo wonder. The predominance of genetic and phenotypic influence on seed germination to the detriment of environmental impact, even in high temperatures, allows the continuity of bell pepper production in thermal conditions above 30.0 °C, mainly for the cultivars All big and Yolo wonder.